Nove možnosti geodetske stroke - pogled s perspektive negeodeta - Pogačnik, Andrej (Geodetski vestnik, 1998)
Extremely rapid technological development has limited the traditional scope ofgeodesy, requiring geodesists to focus on new fields of scientific and professional activity. Land development in Slovenia will take place in entirely new conditions of private ownership, marketing, legal and administrative frameworks, enforcement of the public interest etc. A new role for the geodetic profession is also required due to new forms, such as dispersed urbanisation, fragmentation, mosaic land use patterns, multiple land use, urbanisation of the countryside, counter-urbanization, agricultural development, etc., which are appearing throughout Europe. In these conditions, geodesists will have to create an important place for themselves among other professionals dealing with land development. The paper presents new fields of surveying activity in greater detail and the knowledge and experience required for them
Keywords: geodezija; razvoj; vloga; zemljišča